The Effect Of Hypoxic Training On Some Blood Components And Some Biochemical Variables In Basketball Players - Omar Fadhil Omar, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The aim of the research is to identify the extent of the effect of hypoxic training on some biochemical variables in the research sample, and to identify the effect of hypoxic training on some blood components in the research sample. The researcher used the experimental method to suit the nature of this research, using a one-group experimental design with a pre- and post-test. The research population and sample were chosen intentionally and were represented by the students of the Specialized Basketball School. The size of the population reached (14) players, and (8) players were chosen to represent the research sample. Thus, the percentage of the research population reached (57%). After conducting the experiment and processing the results statistically, analyzing and discussing them, the researcher concluded that hypoxic exercises have a major role in developing and increasing the proportion and number of red blood cells in the blood, and that hypoxic exercises have a clear effect in increasing the proportion of hemoglobin in the blood, and the proportion of red blood cells in the blood as a whole developed as a result of applying hypoxic exercises, which are characterized by a lack of oxygen. Hypoxic exercises have a major role in increasing the volume of red blood cells and increasing the percentage of oxygen in the blood as a result of the hypoxic exercises used in the research. In light of the previous conclusions, the researcher recommends informing the trainers of the importance of hypoxia and using their own training units, and adopting the exercises prepared by the researcher in the training and use Hypoxic to bring about skill, physical and biochemical development. The researcher recommends to conduct similar studies on different samples and different sporting events, and to conduct comparative studies between boys and girls to find out effects on any gender, to apply hypoxic training and find out its effect physically and skillfully in other research.